Decisional Competence and 'Best Interests': Establishing the Threshold for Fitness to Stand Trial - Brookbanks, W. J.; Mackay, R. D. (Otago Law Review, 2010)
The article discusses the English case law under the notion of best interest test as articulated that lead to the development of fitness to plead in New Zealand. It examines the idea of decisional capacity and its start to turn fitness jurisprudence more decisively towards a capacity-based notion of trial competence. Also mentioned is the developments of case law where the best interest standard is discussed and its future implications on law.